The Council of the Church about the Church - Madrigal Terrazas, SJ, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Today it is frequently claimed that the Second Vatican Council mainly focused on ecclesiological questions. It is necessary, however, to increase our knowledge of how these new conceptions came forth, and how these ecclesiological questions are also present in documents whose theme is not primarily the Church. This article reviews the growing process of the documents of the Council, showing their ecclesiological concentration. Secondly, a summary is offered of the main characteristics that, according to the Council, describe most accurately what the Church is.